The Effectiveness of Digitizing Land Services to Prevent Land Mafia - Artha, Yophinadiyyul Fauqalida; Tri Bawono, Bambang (TABELLIUS: Journal of Law, 2023)
This research aims to analyze: 1) Implementation of digitization of land services. 2) Effectiveness of digitizing land services to prevent land mafia. The approach method used in this research is a sociological juridical approach. The research specifications used are analytical descriptive research. This type of data uses primary data and secondary data obtained through interviews and literature study. The data analysis method used in this research is descriptive analysis. The research results were concluded: 1). Implementation of digitization of land services is carried out through the website www.bpn.go.id. Currently the ATR/BPN Ministry has implemented four digital land services, including Electronic Mortgage Rights (HT-El), certificate checking, Land Registration Certificate (SKPT), and Land Value Zone information. There are two electronic services that will be added by the ATR/BPN Ministry, namely land sale and purchase deeds and transfer of rights. The implementation of digitalization of land services at BPN Ngawi, apart from the website www.bpn.go.id, is also carried out through the Touch Tanahku application. Touch My Land is an application created to answer various community land problems. 2) The effectiveness of digitizing land services to prevent land mafia can effectively prevent land mafia practices and achieve the strategic goals of the ATR/BPN ministry. Keywords: Digitalization; Land; Mafia; Registration.